Insights into pathophysiology of smoke-related cardiovascular disease - Salvatore De Rosa; Mario Pacileo; Laura Sasso; Vito Di Palma; Paola Maietta; Antonella Paglia; Linda Brevetti; Plinio Cirillo; Massimo Chiariello (Monaldi Archives for Chest Disease, 2016)
cardiovascular morbidity and mortality are well established. Both active and passive smoking represent a major health hazard for both men and women. The great concerns related to the deleterious effects of CS on cardiovascular disease have been translated into various kinds of social interventions and targeted health policies since ever. The high health impact of cigarette smoking has driven a huge number of researches at the epidemiological, clinical and biological level. Nevertheless, even though many progresses have been made in understanding the mechanisms underlying the high disease burden associated to cigarette smoke, the exact components and the mechanisms by means of which it exerts its effects remain to be completely clarified as yet. The present paper reviews the main observations on the pathophysiology of smoke-related cardiovascular diseases, providing an up-to-date perspective about one of the main cardiovascular killers of our days.